Kemaslahatan Manusia Sebagai Puncak Maqāṣid al-Qur`ān: Tinjauan Terhadap Konsep Maqāṣid al-Qur`ān Abd al-Karīm Hāmidī - Noor, M. Fahrian; Wahyuni, Yuni; Samsuri, Bisri (Al-Qudwah, 2023)
The article discusses the theory of maqāṣid al-Qurān conceptualized by Abd al-Karīm Hāmidī, which leads to the concept of human welfare (al-maṣlahah). There are several developments from the concepts of his predecessors, such as Rasyid Riḍa, Mahmūd Syaltūt, and Ibn Āsyūr, formulated in their concept of maqāṣid al-Qurān. Hāmidī extensively elaborates on the maqāṣid al-Qurān oriented towards the welfare of individuals, society, and nature. The discussion in this article will focus on answering two questions: first, what is the concept of maqāṣid al-Qurān according to Abd al-Karīm Hāmidī, and second, what is the purpose of maqāṣid al-Qurān in relation to maqāṣid al-syarīah. This research is a type of literature study using a descriptive-analytical method. The researcher will describe Hāmidī's thoughts on maqāṣid al-Qurān and then analyze the concept of al-maṣlahah he intended. The findings of this study show that maqāṣid al-Qurān has a hierarchy consisting of al-maqāṣid al-āmmah, which is the overall wisdom of the Qur’an covering: the goals of individual goodness, the goals of social and community welfare, and the goals of worldly goodness. Al-maqāṣid al-khāṣsah, specifically the shariah, which includes the goals of improving the mind, self, body, family, wealth, law, legislation, and politics. Then, al-maqāṣid al-juz’iyyah, meaning, and rules related to laws that stand alone, such as the goal of purification, facing the qibla, prayer times, and others. The three aspects of maqāṣid al-Qurān have one goal, which is to realize the welfare and goodness of humanity on this earth. Additionally, there is a continuity between the concept of maqāṣid al-Qur`ān proposed by Hāmidī and the concepts in maqāṣid al-syarīah formulated by Muslim scholars before him.  Abstrak: Tulisan ini membahas tentang teori maqāṣid al-Qur`ān yang dikonsepsi oleh Abd al-Karīm Hāmidī yang berujung kepada kemaslahatan manusia (al-maṣlahah). Ada beberapa pengembangan dari para konsep para pendahulunya seperti Rasyid Riḍa, Mahmūd Syaltūt dan Ibn `Āsyūr yang dirumuskan dalam konsep maqāṣid al-Qur`ān-nya. Hāmidīmenjelaskan panjang lebar tentang maqāṣid al-Qur`ān yang berorientasi kepada kemaslahatan manusia secara individu, masyarakat dan alam. Adapun pembahasan dalam tulisan ini akan terfokus untuk menjawab pertanyaan; pertama, bagaimana konsep maqāṣid al-Qur`ān menurut Abd al-Karīm Hāmidī; dan kedua, apa tujuan dari maqāṣid al-Qur`ān tersebut dalam kaitannya dengan maqāṣid al-syarīah. Penelitian ini merupakan jenis penelitian pustaka dengan menggunakan metode deskriptif-analitis. Peneliti akan mendeskripsikan pemikiran Hāmidī tentang maqāṣid al-Qur`ān kemudian menganalisis seperti apa konsep al-maṣlahah yang dimaksudkannya. Temuan dari penelitian ini memaparkan bahwa maqāṣid al-Qur`ān memiliki hierarki yang terdiri dari al-maqāṣid al-`āmmah, merupakan hikmah keseluruhan Al-Qur’an yang mencakup: tujuan kebaikan individu, tujuan memperoleh kebaikan sosial dan masyarakat dan tujuan memperoleh kebaikan dunia. Al-maqāṣid al-khāṣsah, syariat secara khusus yang mencakup tujuan memperbaiki pikiran, diri, jasad (badan), keluarga, harta, hukum, undang-undang, dan politik. Kemudian al-maqāṣid al-juz’iyyah, merupakan makna dan aturan yang terkait dengan hukum yang berdiri sendiri seperti tujuan bersuci, menghadap kiblat, waktu salat dan lain-lain. Ketiga aspek maqāṣid al-Qur`ān itu memiliki satu tujuan yaitu mewujudkan kemaslahatan dan kebaikan manusia di muka bumi ini. Selain itu terdapat kesinambungan antara konsep maqāṣid al-Qur`ān yang digagas oleh Hāmidī dengan konsep-konsep dalam maqāṣid al-syarīah yang telah dirumuskan oleh cendekiawan muslim sebelumnya.